Pharmacotherapeutic Actions of Essential Oils in Endocrine Disorders: : A Systematic Review (CIPEEX, 2025)
Introduction: Essential oils have attracted attention for their pharmacological properties, particularly regarding modulation of endocrine functions and hormonal balance. Their bioactive compounds act on metabolic and reproductive pathways, suggesting potential for complementary pharmacotherapy in endocrine disorders. Objective: This systematic review aimed to analyze the pharmacotherapeutic effects of essential oils on endocrine-related conditions, identifying biological mechanisms, clinical outcomes, and research gaps. Methods: A systematic search was conducted in PubMed, Scopus, Web of Science, and SciELO databases for articles published between 2000 and 2025. Studies included preclinical and clinical research assessing the effects of essential oils on endocrine parameters. Screening followed PRISMA guidelines, and data were synthesized narratively due to heterogeneity of study designs. Results: Evidence indicated that essential oils such as lavender, clove, cinnamon, and fennel influence insulin secretion, glucose metabolism, thyroid activity, and reproductive hormones. Preclinical studies revealed antioxidant and anti-inflammatory pathways contributing to improved endocrine regulation. Clinical findings, though limited and methodologically diverse, suggested benefits in metabolic syndrome, polycystic ovary syndrome, and menopausal symptoms. Nevertheless, variations in dosage, formulations, and sample sizes restricted generalization of results. Conclusion: Essential oils represent promising adjuvant agents in endocrine pharmacotherapy, with potential applications in metabolic and reproductive disorders. However, current evidence is insufficient to establish standardized therapeutic protocols, and further well-designed clinical trials are necessary to confirm efficacy and ensure long-term safety.